Exo-miRExplorer: A Comprehensive Resource for Exploring and Comparatively Analyzing Exogenous MicroRNAs - Zheng, Ling-Ling; Deng, Kai-Wen; Deng, An-Cheng; Wu, Jie; Yang, Jian-Hua; Lun, Zhao-Rong; Qu, Liang-Hu (Frontiers in Microbiology, 2017)
MicroRNAs (miRNAs) are small regulatory RNAs that play important roles in animals, plants and viruses. Deep-sequencing technology has been widely adopted in miRNA investigations. However, it is still a big mysterious why nearly all sequencing data contain miRNA sequences from exogenous species, called exo-miRNAs. In this study, we developed a novel platform, exo-miRExplorer, for mining and identifying exo-miRNAs from high-throughput small RNA sequencing experiments which originated from tissues and cell lines of multiple organisms. Thousands of exo-miRNAs are characterized with their expression abundance, the RNA families, original organisms and the sequencing platforms presented in exo-miRExplorer. Subsequently, we used exo-miRExplorer to perform further analysis. Comparative analysis of the exo-miRNAs between different sequencing datasets revealed significant correlation of exo-miRNAs between experiments in the same study. The plant-derived exo-miRNAs analysis provided robust evidence for non-diet source of exo-miRNAs. Virus-derived exo-miRNA analysis showed that pathogen RNAs could transfer to host cells and exist in deep-sequencing result at abundance level. In conclusion, exo-miRExplorer provides users with an integrative resource to facilitate detection and analysis of exo-miRNAs. exo-miRExplorer is available at the following URL: http://rna.sysu.edu.cn/exomiRDB/.